Managing and manifesting memory - Jaso, Jacob Stuart, author; Lundberg, Thomas, advisor; Lehene, Marius, committee member; Kissell, Kevin, committee member; Ryan, Ajean, committee member (Colorado State University. Libraries, 2020)
To understand my relationship with my past, I make objects with a sense of urgency to harvest sensations and reveal truths hidden in memory. When I left New Brunswick to emigrate back to the United States, I began to feel a longing to return to Canada. I had found a real sense of home, with deeply personal and profound connections to people and places. I would not truly understand the depth of those connections until I left. As I work to gain perspective on my longing to return to the past, I draw upon Suprematist concepts of creating irrational spaces and giving primacy to feelings over objective visual representation. Both concepts use color and shape to create these irrational spaces and to capture raw emotion. Far from New Brunswick and the people that made me feel welcome, everything I began to make echoed their faces and the landmarks that ground my remembered experiences. To understand the extent and power of memories in my creative process, I considered how to diminish their ability to influence my practice, since everything I made was centered on the past. Could Suprematist strategies offer real ways to distill a memory without diluting the remembered experience, breaking down memory, and discovering truth within the process of longing? If I could not return to living in a comforting past, I would create a window, a portal, a way to dwell in the contentment of that chapter of my life.
Keywords: mixed media; fiber arts; textile arts